THE ROLE OF ROAD TRAFFIC LAWS IN INCREASING COMPETITIVENESS AND OVERCOMING VIOLATIONS - Lookman, Kyatmaja (Lex Prospicit, 2024)
This research analyzes the role of the Road Traffic and Transportation Law in increasing the competitiveness of trucking companies and also addressing violations committed. Transport companies are part of another company's supply chain. Not all trucking companies deal with the goods owner directly, some are through third-party intermediaries (brokers). Tiered transactions are the structure of this industry because there are several levels of parties between the carrier company and the owner of the goods. Field phenomena show that this condition has not yet been achieved. This research aims to discover existing problems with existing laws for future improvements. This research uses normative juridical methods by studying existing laws and conducting comparative studies. Secondary data is also used to obtain the desired results. The results show that current laws cannot increase competitiveness and optimally prevent violations committed by trucking companies. Therefore, future legislation must be able to solve this problem.